Gemcitabine as Salvage Treatment in Patients with Poorly Differentiated Pancreatic Neuroendocrine Tumors: A Case Series - Saif, Muhammad Wasif; Kaley, Kristin; Rodriguez, Teresa; Garcon, Marie Carmel (JOP. Journal of the Pancreas, 2014)
Context Poorly differentiated neuroendocrine carcinoma of the pancreas is a rare and aggressive tumor. The combination of etoposide and cisplatin is considered as the first-line treatment, but no recommendations exist for further treatment after progression. Case series We report here case series of three patients who received gemcitabine as salvage chemotherapy in patients with poorly differentiated neuroendocrine carcinoma of the pancreas. All the three patients achieved clinical benefit with manageable toxicities. The survival was 5.5, 8, and 9 months respectively after the beginning of gemcitabine in these three patients. Conclusions This case series of patients with poorly differentiated neuroendocrine carcinoma of the pancreas who received gemcitabine as salvage chemotherapy suggests that gemcitabine could be an effective salvage treatment. Future studies to investigate gemcitabine in this setting are warranted. Image: Gemcitabine.